Nasally-Administered Oxytocin Has Limited Effects on Owner-Directed Attachment Behavior in Pet Dogs (Canis lupus familiaris) - Thielke, Lauren E.; Rosenlicht, Giovanna; Saturn, Sarina R.; Udell, Monique A. R. (Frontiers in Psychology, 2017)
The present study explored the effects of intranasal oxytocin, a naturally occurring hormone, on the behavior of pet dogs during an attachment test. Each dog participated in two testing sessions. On one visit saline was administered nasally, and on another, oxytocin was administered nasally. Condition order was counterbalanced and a double-blind methodology was employed. Following a 30-minute wait period after administration of solutions, dog-owner pairs participated in the Secure Base Test, a short attachment test consisting of three two-minute phases: (1) Baseline- the owner was present, dogs were able to freely explore the testing room (2) Alone- dogs were left alone in the testing room (3) Return- owners re-entered the room and were reunited with their dog. In each phase the dog was evaluated for contact seeking, exploration, and avoidance behaviors. Although oxytocin administration was expected to increase owner-directed proximity and contact seeking behavior, this effect was not observed. In fact, in the baseline phase, dogs spent significantly more time seeking the proximity of their owners when they received saline than when they received OT (p < 0.05). Sex differences were also assessed for the behavioral variables of interest in the Secure Base Test, and results indicated that OT did not affect dogs’ behavior in the alone phase, but when saline was administered, females spent significantly more time in contact with the door than males in the alone phase (p < 0.05). Overall, the effects of nasally administered oxytocin on attachment related behavior appeared to be limited or inconsistent for this pet dog population.